Dynamic use of coastal areas by bull sharks and the conciliation of conservation and management of negative human–wildlife interactions. Issue 10 (16th July 2021) - Mourier, Johann; Soria, Marc; Blaison, Antonin; Simier, Monique; Certain, Grégoire; Demichelis, Angélique; Hattab, Tarek
Abstract: Knowledge about spatial and temporal variability in the distribution and abundance of predators is necessary to adapt measures to mitigate human–wildlife interactions. Acoustic telemetry and network analyses were used to investigate the spatial ecology of bull sharks, the species responsible for most shark bites in Reunion Island, one of the world's shark bite hotspots. The west coast of the island was not used uniformly by every individual, with size predicting the movements of sharks along the coast. Node‐based metrics – closeness, node strength, and cumulated continuous residency times – derived from up to 181 monthly movement networks from 20 individuals, revealed that smaller sharks (<250 cm total length) primarily used the south‐west coast while larger individuals spent most of their time in the northern region with regular visits to multiple areas along the coast. This study provides essential knowledge on bull shark behaviour and central areas used at different periods of the year, which correlates well with the dynamics of observed shark bites. Our approach provides a non‐invasive alternative to help predicting and anticipating human–shark conflicts and avoid shark culling programmes detrimental to the conservation of large predators such as sharks.